Rancang Bangun Sistem Antrian Pintar Klinik Gigi Menggunakan Raspberry Pi - Ardi Gunawan; Sasmitoh Rahmad Riady; Ismasari Nawangsih; Rianti Kinasih (Faktor Exacta, 2023)
Large-Scale Social Restrictions were imposed in Indonesia in 2020 as a response to the 2019 coronavirus disease (Covid-19), which has become a pandemic, including in Indonesia. The government's appeal regarding social distancing has made many dental clinics move to provide excellent service while still paying attention to social distancing policies. implementation of new policies and ways to overcome challenges by minimizing physical contact while still running business optimally and meeting patient needs. Before the pandemic occurred, patients were required to take a queue number first at the service location and then wait for the number to be called. Under the current conditions, in the midst of the COVID-19 pandemic, you must avoid crowds and maintain physical distance when interacting socially. In the description of the problem, we propose a smart queue as a solution to avoid crowds when going to the dentist's office. Smart Queuing System based on IoT with a Raspberry Pi camera capable of scanning QR codes as validation and a Raspberry Pi serving as a queue validation data server. This system will be used for online queues at dentist clinics. An online registration system determines whether registration is open or closed at the time of registration. With this system, it is hoped that online registration will be more efficient and orderly.